EEG in Prediction of Early Neurodevelopment of Preterm Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at Anjo Kosei Hospital and other centers in Japan and at Washington University, St Louis, MO, USA studied the prognostic value of conventional EEG for the identification of preterm infants admitted to the Anjo neonatal ICU and at risk for adverse neurodevelopment.